Antiosteoporotic Effect of Combined Extract of Morus alba and Polygonum odoratum - Sungkamanee, Sudarat (Hindawi Publishing Corporation, 2014)

(untitled) (Oxid Med Cell Longev)
Due to the limitation of osteoporosis therapy, the alternative therapies from natural sources have been considered. In this study, we aimed to determine the antiosteoporotic effect of the combined extract of Morus alba and Polygonum odoratum leaves. Ovariectomized rats, weighing 200–220 g, were orally given the combined extract at doses of 5, 150, and 300 mg·kg(−1) BW for 3 months. At the end of study, blood was collected to determine serum osteocalcin, calcium, and alkaline phosphatase level. In addition, tibia bone was isolated to determine bone oxidative stress markers, cortical bone thickness, and density of osteoblast. The combined extract decreased oxidative stress and osteoclast density but increased osteoblast density and cortical thickness. The elevation of serum calcium, alkaline phosphatase, and osteocalcin was also observed. These results suggested the antiosteoporotic effect of the combined extract via the increased growth formation together with the suppression of bone resorption. However, further studies concerning chronic toxicity and the underlying mechanism are required.